A through-thickness damage regularisation scheme for shell elements subjected to severe bending and membrane deformations. (February 2019) - Costas, Miguel; Morin, David; Hopperstad, Odd Sture; Børvik, Tore; Langseth, Magnus
Abstract: This research work proposes and validates a damage regularisation model for shell elements used in large-scale simulations. The model evaluates the ratio of bending to membrane loading in the elements based on the through-thickness gradient of the through-thickness plastic strain. The Cockcroft–Latham failure criterion is adopted, whose parameters are modified according to the length-to-thickness ratio of the shell elements in order to reduce the mesh dependency. This regularisation scheme is validated against experimental component tests on a double-chamber profile in an AA6005-T6 recrystallised aluminium alloy under quasi-static and impact loading conditions. The results show that the model is able to accurately predict fracture initiation under all tested conditions.